A respeito da identidade e de sujeitos estigmatizados - Sueli Maria Cabral; Neusa Maria Bongiovanni Ribeiro; Geraldine Alves Santos (Ciências Sociais Unisinos)
This paper analyses the relation between identity and the stigmas which are connected to the people that somehow deal with trash, emphasizing features in the studies related to the contemporary subjects and their identifications, within their own social transformation. The methodological procedures adopted were: from the point of view of the form of the problem’s approach, a qualitative paradigm was chosen; with regards to their objectives, the research has an explanatory approach, and as a technical procedure, the field research was chosen. In order to analyze the testimonials collected from the Social Representation Theory, the main features of the Collective Subject Approach methodology was used. Finally, it has been noticed that working with trash has an impact on the constitution of its processes of emancipation and identification.